2018
DOI: 10.1021/acssuschemeng.8b01926
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sodium Niobate-Based Lead-Free Ceramics as New Environment-Friendly Energy Storage Materials with High Energy Density, High Power Density, and Excellent Stability

Abstract: Recently, ceramic capacitors with fast charge–discharge performance and excellent energy storage characteristics have received considerable attention. Novel NaNbO3-based lead-free ceramics (0.80NaNbO3-0.20SrTiO3, abbreviated as 0.80NN-0.20ST), featuring ultrahigh energy storage density, ultrahigh power density, and ultrafast discharge performance, were designed and prepared in this study. These 0.80NN-0.20ST ceramics exhibited a high breakdown strength of 323 kV/cm, attributable to their small grain size and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 281 publications
(85 citation statements)
references
References 64 publications
4
80
1
Order By: Relevance
“…Some NN‐based solid solutions were reported to exhibit stable AFE orthorhombic P phase at RT, yet extremely large phase switching hysteresis was observed, in addition to their relatively low E B and W rec . Of importance is that improved W rec can be attained in NN‐based solid solutions with a relatively slim P–E loop at high applied electric fields; however, the structure–property relationship is yet unclear. In this work, the NN–BNT solid solution bulk ceramics were fabricated via a conventional high‐temperature solid‐state reaction method.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Some NN‐based solid solutions were reported to exhibit stable AFE orthorhombic P phase at RT, yet extremely large phase switching hysteresis was observed, in addition to their relatively low E B and W rec . Of importance is that improved W rec can be attained in NN‐based solid solutions with a relatively slim P–E loop at high applied electric fields; however, the structure–property relationship is yet unclear. In this work, the NN–BNT solid solution bulk ceramics were fabricated via a conventional high‐temperature solid‐state reaction method.…”
Section: Introductionmentioning
confidence: 68%
“…NaNbO 3 (NN) as a lead‐free AFE material has recently received resurgent attention for energy‐storage applications . However, its AFE P phase with a Pbma space group is not stable at room temperature (RT) and tends to irreversibly transform to FE phase in response to a large external electric field.…”
Section: Introductionmentioning
confidence: 99%
“…4). Compared with state-of-the-art lead-free bulk ceramics 17,20,24,25,29,[40][41][42][43][44][45][46][47][48][49] , the ANT55 exhibits more attractive energy storage performance with both high energy storage density and efficiency, as shown in Fig. 4d.…”
Section: Resultsmentioning
confidence: 99%
“…The pyroelectric coefficient was measured by Byer‐Roundy method after several heating/cooling cycles. Other experimental details not mentioned in this study can be found in our previous published papers …”
Section: Methodsmentioning
confidence: 99%
“…Other experimental details not mentioned in this study can be found in our previous published papers. 32,37,38 3 | RESULTS AND DISCUSSION…”
Section: Methodsmentioning
confidence: 99%